Analisis Teori Herzberg Terhadap Motivasi Kerja Di Lembaga Pendidikan - Lia Amelia; Sitti Chadidjah (CV. ITTC INDONESIA, 2026)
The decline in teacher work motivation is a crucial problem in the implementation of education. An unsupportive work environment, excessive administrative demands, and low salaries and honorariums encourage teachers to perform dual roles, which ultimately have implications for the quality of performance and professionalism. This study aims to examine teacher work motivation in educational institutions through the perspective of Herzberg's Two-Factor Theory, which distinguishes between hygiene factors and motivator factors. This study uses a qualitative approach with a library research method through a review of books, scientific journals, and relevant academic articles. The results of the study indicate that hygiene factors, such as work environment conditions, school policies, compensation systems, and administrative workloads, have a dominant role in suppressing teacher job dissatisfaction. Meanwhile, motivator factors, which include recognition, professional responsibility, and opportunities for competency and career development, directly influence the sustainable improvement of teacher work motivation. This study concludes that increasing teacher work motivation can only be achieved through a strategic combination of fulfilling hygiene factors and strengthening motivator factors. These findings are expected to serve as a reference for educational institution managers in formulating policies to improve teacher motivation and performance comprehensively and sustainably.